Pengaruh Return On Equity (ROE) dan Total Asset Turnover (TATO) terhadap Pertumbuhan Laba pada Perusahaan Healthcare yang Terdaftar di BEI Periode 2019-2023 - Delisa Puspitasari; Furi Indriyani; Rohani Lestari Napitupulu (PPIMAN Pusat Publikasi Ilmu Manajemen, 2025)
Profit growth serves as a primary benchmark for evaluating financial standing, particularly within the healthcare industry which demands elevated levels of efficiency and superior financial stewardship. As healthcare companies face increasingly competitive environments and high operational costs, the ability to generate sustainable profits becomes a critical determinant of long-term viability. This study aims to examine the impact of Return on Equity (ROE) and Total Asset Turnover (TATO) on the profit growth of healthcare companies registered on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The research employed a quantitative approach using secondary data, with a sample of 10 companies selected through purposive sampling. Data analysis was conducted using multiple linear regression, supported by classical assumption testing, t-tests, F-tests, and the coefficient of determination (R²). The results revealed that ROE had a positive and partially significant effect on profit growth, while TATO showed a positive but not significant influence. However, when tested simultaneously, both variables demonstrated a significant relationship, with the model explaining 23.9% of the variance in profit growth. These findings suggest that profitability ratios, particularly ROE, play a more decisive role in determining financial performance in healthcare companies compared to activity ratios. The study highlights the importance for healthcare firms to optimize equity utilization in order to enhance sustainable profit growth and shareholder value.